Киберпанкот и слободното толкување на стварноста - Ноневски, Вангел (Филозофско друштво на Македонија - Скопје, 2019)
The text offers a particular contextualisation of the theoretical research of cyberpunk narratives and hermeneutics. The science-fiction subgenre of cyberpunk is taken as a narrative paradigm because of its intrinsic treatment of reality, perception and memory. In its topics of interest, set design and iconography we recognize an “acceleration” of the main concerns of the critical theory of neoliberal capitalism: subordination caused by the metastasis of global consumerism, sophisticated construction of reality in cyberspace, simulated desires and needs in the agenda of reproduction of capital, etc. Three modes of the concept of cyberspace in the narrative of cyberpunk are examined: cyberspace as virtual reality, cyberspace as our reality and cyberspace as a medium for interpenetration of those realities. The problems of reality, perception, desire and freedom are extracted as key in a Marxist reading of cyberpunk, concluding that what we call “reality” should not be treated as something “out there” (or objective), but rather as a platform for expanding the possibilities for proactive and/or virtual construction of reality.
Cyberpunk and Free Interpretation of Reality
Keywords: cyberpunk, film, virtual reality, perception, Marxism, memory, neoliberalism, interpretation